Pyrolysis of biomass to produce H-rich gas facilitated by simultaneously occurring magnesite decomposition - Mengjuan Zhang; Cong Zhang; Binwenbo Zhu; Chao Wang; Xin Jia; Guoqing Guan; Xi Zeng; Erfeng Hu; Zhennan Han; Guangwen Xu (Carbon Resources Conversion, 2025)
This study investigated how biomass pyrolysis varies with the different fractions of magnesite mixing into biomass. The pyrolysis occurred with simultaneous decomposition of magnesite without use of any gasification reagent, and was analyzed in terms of producer gas yield and quality. As magnesite fraction increased from 0 to 30 %, the yield of producer gas and its calorific value increased from 48.6 % to 66.3 % and 8.29 to 8.93 MJ/Nm3, respectively. The carbon and hydrogen conversion increased from 44.1 % to 60.7 % and 43.1 % to 66.2 %, respectively. The characterization results revealed that magnesite particles facilitated the conversion of fixed carbon and the thermal/catalytic cracking of tar to produce H-rich gas. The in-situ generated CO2 from magnesite decomposition could be reduced to CO/CH4 in the reductive atmosphere of the pyrolysis products. This study proposes the concept of converting low-energy–density biomass into gas without oxygen and provides a novel approach for producing H-rich gas from biomass.